2013
DOI: 10.1590/1414-431x20132647
|View full text |Cite
|
Sign up to set email alerts
|

A spheroid-based 3-D culture model for pancreatic cancer drug testing, using the acid phosphatase assay

Abstract: Current therapy for pancreatic cancer is multimodal, involving surgery and chemotherapy. However, development of pancreatic cancer therapies requires a thorough evaluation of drug efficacy in vitro before animal testing and subsequent clinical trials. Compared to two-dimensional culture of cell monolayer, three-dimensional (3-D) models more closely mimic native tissues, since the tumor microenvironment established in 3-D models often plays a significant role in cancer progression and cellular responses to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 35 publications
7
61
0
3
Order By: Relevance
“…Specifically, Wen et al [14] reported that 3D cultures (in Matrigel) of MIAPaCa-2 and PANC-1 pancreatic cancer cell lines, when treated with gemcitabine and 5-FU, had a higher resistance to the effects of these drugs in comparison to cells grown in 2D. Similarly, Ponce de León et al .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Wen et al [14] reported that 3D cultures (in Matrigel) of MIAPaCa-2 and PANC-1 pancreatic cancer cell lines, when treated with gemcitabine and 5-FU, had a higher resistance to the effects of these drugs in comparison to cells grown in 2D. Similarly, Ponce de León et al .…”
Section: Discussionmentioning
confidence: 99%
“…The main optimizations, practical, and troubleshooting approaches described in the literature for this technique will be overviewed hereafter (Figure 2). 2-Methoxyestradiol Glioblastoma U87MG [20] 5-Fluorouracil Pancreatic cancer MIAPaCa-2 [94] Panc-1 [94] Mercaptopurine (6-MP and 6-MPR)…”
Section: Optimization Of the Methodsology Used To Form 3d Spheroids Thmentioning
confidence: 99%
“…Active cell proliferation is sometimes required for some drugs to be effective. 63 Examples of drugs that require active proliferation to be effective are 5-fluorouracil (5-FU) and doxorubicin. Tung et al 64 showed that the lack proliferating cells in A431.H9 3D…”
Section: Cell Cultures In Drug Discoverymentioning
confidence: 99%